Long-term, open-label extension study of the efficacy and safety of epicutaneous immunotherapy for peanut allergy in children: PEOPLE 3-year results - Fleischer, David M.; Shreffler, Wayne G.; Campbell, Dianne E.; Green, Todd D.; Anvari, Sara; Assa'ad, Amal; Bégin, Philippe; Beyer, Kirsten; Bird, J. Andrew; Brown-Whitehorn, Terri; Byrne, Aideen; Chan, Edmond S.; et al. (Journal of Allergy and Clinical Immunology, 2020)
Background: The PEPITES (Peanut EPIT Efficacy and Safety) trial, a 12-month randomized controlled study of children with peanut allergy and 4 to 11 years old, previously reported the safety and efficacy of epicutaneous immunotherapy (EPIT) for peanut allergy (250 μg, daily epicutaneous peanut protein; DBV712 250 μg). Objective: We sought to assess interim safety and efficacy of an additional 2 years of EPIT from the ongoing (5-year treatment) PEOPLE (PEPITES Open-Label Extension) study. Methods: Subjects who completed PEPITES were offered enrollment in PEOPLE. Following an additional 2 years of daily DBV712 250 μg, subjects who had received DBV712 250 μg in PEPITES underwent month-36 double-blind, placebo-controlled food challenge with an optional month-38 sustained unresponsiveness assessment. Results: Of 213 eligible subjects who had received DBV712 250 μg in PEPITES, 198 (93%) entered PEOPLE, of whom 141 (71%) had assessable double-blind, placebo-controlled food challenge at month 36. At month 36, 51.8% of subjects (73 of 141) reached an eliciting dose of ≥1000 mg, compared with 40.4% (57 of 141) at month 12; 75.9% (107 of 141) demonstrated increased eliciting dose compared with baseline; and 13.5% (19 of 141) tolerated the full double-blind, placebo-controlled food challenge of 5444 mg. Median cumulative reactive dose increased from 144 to 944 mg. Eighteen subjects underwent an optional sustained unresponsiveness assessment; 14 of those (77.8%) maintained an eliciting dose of ≥1000 mg at month 38. Local patch-site skin reactions were common but decreased over time. There was no treatment-related epinephrine use in years 2 or 3. Compliance was high (96.9%), and withdrawals due to treatment-related adverse events were low (1%). Conclusions: These results demonstrate that daily EPIT treatment for peanut allergy beyond 1 year leads to continued response from a well-tolerated, simple-to-use regimen.
CRIS-Team Scopus Importer:2020-08-21
Keywords: desensitization; eliciting dose; epicutaneous immunotherapy; EPIT; food allergy; immunotherapy; Peanut allergy; sustained unresponsiveness